APLIKASI SISTEM E-VOTING KETUA UMUM UPN BAND VETERAN JAKARTA BERBASIS WEBSITE - Anne Theresia Siahaan (2021)
In an organization, information systems are indispensable for getting fast, precise, and accurate information. It is very important especially in voting activities that are generally still done manually, such as in the Student Activity Unit Band of the National Development University Veteran Jakarta. E-voting is a matter that refers to the use of information technology in the implementation of voting. The development of this system is done because looking at the counting of votes that have been manual can take time and see not a few members who are not present at the time of voting. The method used in the study is waterfall method, because it uses a sequential and systematic approach. System design is described with Unified Modelling Language or UML diagrams. This E-voting application is a website-based built using PHP programming language and MySQL storage data (phpMyAdmin). With this application, it will result in more efficient and safe selection.